2020
DOI: 10.1002/ags3.12400
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 5‐year postoperative outcomes after Billroth I and Roux‐en‐Y reconstruction following distal gastrectomy for gastric cancer: Results from a multi‐institutional randomized controlled trial

Abstract: Aim We previously reported in a randomized controlled trial that Billroth I and Roux‐en‐Y reconstructions were generally equivalent regarding body weight change and nutritional status 1 year after distal gastrectomy for gastric cancer. We describe the long‐term follow‐up data 5 years after distal gastrectomy. Methods We analyzed consecutive gastric cancer patients who were randomly assigned to undergo Billroth I or Roux‐en‐Y reconstruction after distal gastrectomy. We evaluated body weight change, nutritional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…On the contrary, Nakanishi et al 22 conducted a control study on 1,014 patients with distal gastric cancer in 2020 and found that the incidence of postoperative complications of Billroth I anastomosis was lower than that of Roux-en-Y anastomosis. Overall, the incidence of reflux esophagitis in patients with Billroth I anastomosis after distal gastrectomy is higher than that in patients with Roux-en-Y anastomosis 5,23 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…On the contrary, Nakanishi et al 22 conducted a control study on 1,014 patients with distal gastric cancer in 2020 and found that the incidence of postoperative complications of Billroth I anastomosis was lower than that of Roux-en-Y anastomosis. Overall, the incidence of reflux esophagitis in patients with Billroth I anastomosis after distal gastrectomy is higher than that in patients with Roux-en-Y anastomosis 5,23 .…”
Section: Discussionmentioning
confidence: 82%
“…However, the common nutritional disorders and anemia after gastrectomy are often ignored by people 4 . When the tumor condition of patients with distal gastric cancer allows the use of different reconstruction methods to complete the operation, which method is more conducive to the improvement of postoperative nutritional status and anemia status, more conducive to improve the quality of life (QoL) of patients, there is still a lack of conclusion [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Tại Nhật Bản, phục hồi lưu thông theo Billroth I thường được áp dụng sau cắt bỏ dạ dày bán phần do ung thư, ngược lại tại Châu Âu và Nam Mỹ hay áp dụng miệng nối Billroth II và Roux-en-Y. [3][4][5] Trên thế giới có nhiều thông báo so sánh giữa hai phương pháp Billroth I và II, Roux-en-Y kết quả khác nhau theo từng nơi, tỷ lệ biến chứng còn phụ thuộc vào các yếu tố khác như: số ca phẫu thuật, phẫu thuật triệt để hay không triệt để, có hay không có nạo vét hạch, kinh nghiệm phẫu thuật viên… [6][7][8][9][10]12 Tại Việt Nam có nhiều nghiên cứu về bệnh lý ung thư dạ dày, tuy nhiên còn ít nghiên cứu riêng về phục hồi lưu thông theo phương pháp Billroth I, kiểu Péan sau cắt dạ dày do ung thư 1/3 dưới. Nghiên cứu này nhằm mô tả đặc điểm lâm sàng cận lâm sàng, giải phẫu bệnh và kết quả sau phẫu thuật cắt đoạn dạ dày cực dưới với miệng nối kiểu Péan cho người cao tuổi bị ung thư 1/3 dưới dạ dày tại Bệnh viện Hữu Nghị Việt Đức.…”
Section: đặT Vấn đềunclassified
“…Although Billroth I was the method of choice for a long time, it is currently accepted that the bile reflux gastritis is best minimized by Roux-en-Y reconstruction [30]. However, until the 21st century, the general preference for TG was to use jejunum loop reconstruction; during the last two decades, Roux-en-Y reconstruction became the standard procedure worldwide [31]. The Roux-en-Y reconstruction following TG is also a preferred method of reconstruction after pancreatic and biliary resections and liver and pancreatic cysts, as well as in bariatric surgery [32].…”
Section: Reconstruction Following Resectionmentioning
confidence: 99%